Supporting paediatric patients: Parental presence in the anaesthetic journey - Salina Blake (Journal of Perioperative Nursing)
Objective: This discussion paper explores the use of parental presence during induction of anaesthesia as a method of decreasing paediatric and parental perioperative anxiety.